THE INFLUENCE OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT TVRI SOUTH SULAWESI STATION - Friska Friska; Hety Budiyanti, Agung Widhi Kurniawan, Muhammad Ichwan Musa, Rezky Amalia Hamka (CV. Adiba Aisha Amira, 2025)
This research aims to determine the influence of compensation and work motivation on employee performance at TVRI South Sulawesi Station. The variables in this research consist of independent variables, namely compensation and work motivation, and the dependent variable, namely employee performance. The population in this study were all employees of TVRI South Sulawesi Station. The sampling technique uses Purposive Sampling technique. The data collection techniques used were questionnaires, interviews, observation and documentation. The data analysis technique used is multiple linear regression analysis with SPSS version 25 software to prove the hypothesis. The results of this research indicate that partial compensation has a significant effect on employee performance at TVRI South Sulawesi Station. Also, work motivation partially has a significant effect on employee performance at TVRI South Sulawesi Station. Then, compensation and work motivation simultaneously have a significant effect on employee performance at TVRI South Sulawesi Station.